Proceso de ASC - PREVALENCIA DE LOS VALORES CRISTIANOS EN EL LIBERALISMO POLITICO CONTEMPORANEO DESPUES DE LA "MUERTE DE DIOS" (2023)
One of the most controversial issues in Friedrich Nietzsche's philosophy is, not surprisingly, the refutation of God and his uselessness in today's society, which he exposes as the "death of God", bringing with it the fall of Christian morality as the hegemonic principle of values. This fall means a nihilistic state in society, because for the author it finds itself with a lack of values when it manages to refute its previous morality, since there is an absence of an entity that judges and determines good and evil; This state and refutation of God is due to various historical and political events, such as the Peace of Westphalia, the Industrial Revolution and the French Revolution, which brought with them new beliefs and ideals, such as the Enlightenment and liberalism as hegemonic political theory which promotes a secular state and a division of this with the church, thus creating a new social paradigm and building a new morality on the destroyed, a morality where man and his individuality as the center of the world and not God. With regard to the above, as researchers we will analyze how true is Nietzsche's assertion that Christian morality is nonexistent as a hegemonic scale of values in today's society.